Mengajarkan Kasih Kristiani di Tengah Keberagaman Budaya dan Agama - Hepni Putri; Presi Nila Sari; Semuel Linggi Topayung (Berkat : Jurnal Pendidikan Agama dan Katolik, 2024)
This article discusses the importance of teaching Christian love amid the cultural and religious diversity in Indonesia. Diversity, which is a national treasure, should be nurtured through inclusive humanitarian values, where every individual is viewed as a fellow being worthy of love and respect. In this context, Jesus' teachings about love for one another and Martin Buber's concept of "I and Thou" play a significant role in fostering mutual respect.The article emphasizes that the biblical teachings on love, particularly in 1 Corinthians 13, serve as a foundation for creating positive and inclusive social interactions. By applying Christian values, society is expected to reduce prejudice and discrimination, as well as prevent conflict. The importance of instilling these values from an early age, both in families and educational institutions, is highlighted as a means to build a generation that is sensitive to differences. Through love and understanding, it is hoped that a harmonious and prosperous Indonesian society can be created, where every individual feels valued regardless of their background.